The Effects of the Crohn’s Disease Exclusion Diet on the Clinical Course of Inflammatory Bowel Diseases in Pediatric and Adult Populations - Woźniacka, Agnieszka; Piechowicz , Agnieszka; Bryksy, Sylwia; Tymchenko, Hanna; Marciszewska, Aleksandra; Świątecka, Martyna; Kaźmierczyk, Jakub; Jopek, Jakub; Popczyk, Michał; Buczkowska, Ewa (Quality in Sport, 2026)
Introduction: Crohn’s disease is a chronic inflammatory condition of the gastrointestinal tract and a major subtype of inflammatory bowel disease (IBD). Its multifactorial etiology involves genetic, immunological, and environmental factors, among which diet plays a key role in modulating gut microbiota and intestinal barrier function. Aim of the study: This narrative review aims to evaluate the role of dietary interventions in Crohn’s disease, with particular emphasis on the effectiveness of the Crohn’s Disease Exclusion Diet (CDED) in inducing and maintaining remission. Materials and methods: A comprehensive literature review was conducted using Google Scholar and scientific databases. The analysis included randomized controlled trials, prospective and retrospective studies, and experimental research focusing on the impact of dietary interventions, particularly CDED, on clinical outcomes in patients with Crohn’s disease. Results: The reviewed studies indicate that CDED, especially when combined with partial enteral nutrition (PEN), is effective in inducing clinical remission and reducing inflammatory markers. Compared to exclusive enteral nutrition (EEN), CDED demonstrates better patient adherence and tolerability. Additionally, the diet positively influences gut microbiota composition and intestinal barrier integrity. Conclusions: CDED appears to be a promising dietary strategy in the management of Crohn’s disease. However, despite encouraging results, further large-scale and long-term studies are required to confirm its effectiveness and establish its role in standard treatment guidelines.